2001
DOI: 10.1007/s002680020372
|View full text |Cite
|
Sign up to set email alerts
|

Determining Which Patients Require Evaluation for Blunt Cardiac Injury following Blunt Chest Trauma

Abstract: The objective of this study was to determine prospectively which risk factors require cardiac monitoring for blunt cardiac injury (BCI) following blunt chest trauma. All patients who sustained blunt chest trauma had an electrocardiogram (ECG) on admission to our urban level I trauma center. Those with ST segment changes, dysrhythmias, hemodynamic instability, history of cardiac disease, age > 55 years, or a need for general anesthesia within 24 hours (group 1) were admitted to the intensive care unit (ICU) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 17 publications
0
28
0
3
Order By: Relevance
“…We hypothesize that the quantity of damaged myocardial cells was not sufficient to increase the circulating levels of troponin T above the clinical detection threshold, or cause echocardiographic features of cardiac injury. This hypothesis is supported by three facts: (1) the myocardial wall architecture of the RV is thinner than the left ventricle (LV) [5,11], (2) several studies have shown that the RV is more frequently injured than the LV in patients with BCI following blunt chest trauma because of the anterior position of the RV in the thorax and its proximity to the sternum [5,10,11], and (3) the impact of the blow to the chest did not cause overwhelming cardiac injury, although a sternal fracture was present.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…We hypothesize that the quantity of damaged myocardial cells was not sufficient to increase the circulating levels of troponin T above the clinical detection threshold, or cause echocardiographic features of cardiac injury. This hypothesis is supported by three facts: (1) the myocardial wall architecture of the RV is thinner than the left ventricle (LV) [5,11], (2) several studies have shown that the RV is more frequently injured than the LV in patients with BCI following blunt chest trauma because of the anterior position of the RV in the thorax and its proximity to the sternum [5,10,11], and (3) the impact of the blow to the chest did not cause overwhelming cardiac injury, although a sternal fracture was present.…”
Section: Discussionmentioning
confidence: 55%
“…ECG abnormalities are frequently demonstrated in patients following blunt chest trauma and can be nonspecific [1,6,9,[10][11][12]. Some of the ECG abnormalities can be mediated by noncardiac factors such as hypoxia, anemia, serum electrolyte disturbances, or changes in vagal or sympathetic tone, particularly in multi-trauma patients [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormalities such as wall motion defects and valvular incompetence are readily recognised. Nagy et al [52] in a prospective analysis of 315 patients, ascertained that the echocardiogram has no added diagnostic utility for patients with normal ECG and blood pressure on admission. Also, the Eastern Association for the Surgery of Trauma recommends selective use of echocardiography for patients, who are haemodynamically unstable or suffer cardiac complications [33].…”
Section: Echocardiogrammentioning
confidence: 99%